2005
DOI: 10.1167/iovs.05-0366
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Machine Learning Classifiers for Glaucoma Detection: A Preliminary Study

Abstract: Automated machine classifiers of OCT data might be useful for enhancing the utility of this technology for detecting glaucomatous abnormality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
109
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(126 citation statements)
references
References 34 publications
8
109
1
1
Order By: Relevance
“…MLC techniques have also been employed with various technologies designed to perform structural and functional evaluation of glaucoma, including TD-OCT (15,17,19,23) , HRT (18,22,24) , GDx (16,20) , and visual field (13,18,20,21) . Several studies have used MLC techniques to combine functional and imaging data in attempt to improve diagnostic accuracy (19,22) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MLC techniques have also been employed with various technologies designed to perform structural and functional evaluation of glaucoma, including TD-OCT (15,17,19,23) , HRT (18,22,24) , GDx (16,20) , and visual field (13,18,20,21) . Several studies have used MLC techniques to combine functional and imaging data in attempt to improve diagnostic accuracy (19,22) .…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing these two technologies have demonstrated that the sensitivity and specificity of various RNFL parameters using the Cirrus OCT are excellent and equivalent to the Stratus OCT (9)(10)(11)(12)(13) . Since 1990 (Goldbaum MH, et al IOVS 1990;31; ARVO Abstract 503), machine learning classifier (MLC) techniques have been applied to optical imaging and visual function measurements to improve glaucoma detection, with results suggesting that these techniques are as good as or better than currently available methods at classifying eyes as glaucomatous or healthy (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) . Classifiers usually employ a form of supervised learning, where the program learns from positive and ne gative training examples, representing cases where, for example, there are signs of glaucoma on data obtained by examination of the visual field (positive examples) or not (negative examples).…”
Section: Sensitivity and Specificity Of Machine Learning Classifiers mentioning
confidence: 99%
“…Measurements of the circumpapillary RNFL are reproducible [7][8][9] and useful in the early diagnosis of glaucoma. [10][11][12][13][14][15][16][17][18][19] Stratus (Carl Zeiss Meditec, Inc., Dublin, CA) is the most widely used OCT system for glaucoma diagnosis. Stratus measures the RNFL thickness profile along a 3.4-mm-diameter circle around the optic disc.…”
mentioning
confidence: 99%
“…SVMs and other machine learning classifiers have previously been used for various classification problems, including automatic and semiautomatic retinal layer segmentation by classifying pixels as belonging to different layers [21,22], glaucoma detection [23][24][25][26][27], and segmentation of the ONH [28]. In this work, we exploit a novel utilization of SVMs to detect the images of diseased eyes in which some retinal layers may be missing.…”
Section: Svmmentioning
confidence: 99%